Effects of a Comprehensive Police Suicide Prevention Program - Mishara, Brian L. (Hogrefe Publishing, 2012)
Background: Police suicides are an important problem, and many police forces have high rates. Montreal police suicide rates were slightly higher than other Quebec police rates in the 11 years before the program began (30.5/100,000 per year vs. 26.0/100,000). Aims: To evaluate Together for Life, a suicide prevention program for the Montreal police. Methods: All 4,178 members of the Montreal police participated. The program involved training for all officers, supervisors, and union representatives as well as establishing a volunteer helpline and a publicity campaign. Outcome measures included suicide rates, pre-post assessments of learning, focus groups, interviews, and follow-up of supervisors. Results: In the 12 years since the program began the suicide rate decreased by 79% (6.4/100,000), while other Quebec police rates had a nonsignificant (11%) increase (29.0/100,000). Also, knowledge increased, supervisors engaged in effective interventions, and the activities were highly appreciated. Limitations: Possibly some unidentified factors unrelated to the program could have influenced the observed changes. Conclusions: The decrease in suicides appears to be related to this program since suicide rates for comparable populations did not decrease and there were no major changes in functioning, training, or recruitment to explain the differences. Comprehensive suicide prevention programs tailored to the work environment may significantly impact suicide rates.